2020
DOI: 10.1186/s12870-020-02477-2
|View full text |Cite
|
Sign up to set email alerts
|

Determining optimal mulching, planting density, and nitrogen application to increase maize grain yield and nitrogen translocation efficiency in Northwest China

Abstract: Background The combination of mulch with N fertilizer application is a common agronomic technique used in the production of rainfed maize (Zea mays L.) to achieve higher yields under conditions of optimum planting density and adequate N supply. However, the combined effects of mulch, planting density, and N fertilizer application rate on plant N uptake and N translocation efficiency are not known. The objective of this study was to quantify the interaction effect of mulch, planting density, and N fertilizer ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 98 publications
1
7
1
Order By: Relevance
“…It concluded that with proper mulching and nitrogen management helped the crop to utilize soil moisture and provided competitive advantage towards the high crop growth, yield attributes that resulted in grain and stover yield. Similar result was also reported by Wang et al (2020) [12] and Qin et al (2021) [14].…”
Section: Effect On Yieldsupporting
confidence: 91%
See 1 more Smart Citation
“…It concluded that with proper mulching and nitrogen management helped the crop to utilize soil moisture and provided competitive advantage towards the high crop growth, yield attributes that resulted in grain and stover yield. Similar result was also reported by Wang et al (2020) [12] and Qin et al (2021) [14].…”
Section: Effect On Yieldsupporting
confidence: 91%
“…Similarly root growth, above ground biomass and the nutritional value of fruits are influenced by proper nitrogen management [11]. The combine application of mulching and nitrogen enhance nutrient composition of soil, along with nutritional value of seeds and stover and economics of the production [12]. Therefore, an experiment was conducted to check the interaction effect of mulching and nitrogen management on the nutritional value of seeds and stover, along with chemical properties of soil and economics.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in IE is associated with an increase in NHI, which in turn was associated with a higher N translocation efficiency in later stages of the grain filling period [31,60]. In our experiment, the NPS rate increase did not lead to the improvement of NHI.…”
Section: Discussioncontrasting
confidence: 45%
“…The advantage of PFP over others results from its sensitivity both to the course of weather and experimental factors. As the literature shows, the PFP values in maize cultivation for grain stay within the range of 6.1 and 114.9 kg kg −1 [14,44,[59][60][61]. Thus, the PFP are within the above-mentioned range, yet they remain quite high.…”
Section: Discussionmentioning
confidence: 78%
“…We found the contents of HN, AP, and AK were generally the highest under MF and MB treatments during the entire shooting period. Additionally, organic fertilizer and bamboo leaves have fast decomposition ability with a high nutrient return to soil [47,48] and can be extremely beneficial to the growth of D. latiflorus Munro.…”
Section: Discussionmentioning
confidence: 99%